Effects of Traumeel (Tr14) on Exercise-Induced Muscle Damage Response in Healthy Subjects: A Double-Blind RCT - Kerstin Muders; Christian Pilat; Vanessa Deuster; Torsten Frech; Karsten Krüger; Jörn Pons-Kühnemann; Frank-Christoph Mooren (Mediators of Inflammation)
The present double-blind, randomized, placebo-controlled clinical trial intended to test whether ingestion of a natural combination medicine (Tr14 tablets) affects serum muscle damage and inflammatory immune response after downhill running. 96 male subjects received Tr14 tablets, which consist of 14 diluted biological and mineral components, or a placebo for 72 h after the exercise test, respectively. Changes in postexercise levels of various serum muscle damage and immunological markers were investigated. The area under the curve with respect to the increase (AUCi) of perceived pain score and creatine kinase (CK) were defined as primary outcome measures. While for CK the p value of the difference between the two groups is borderline, the pain score and muscle strength were not statistically significant. However, a trend towards lower levels of muscle damage (CK, p=0.05; LDH, p=0.06) in the Tr14 group was shown. Less pronounced lymphopenia (p=0.02), a trend towards a lower expression of CD69 count (p=0.07), and antigen-stimulated ICAM-1 (p=0.01) were found in the verum group. The Tr14 group showed a tendentially lower increase of neutrophils (p=0.10), BDNF (p=0.03), stem cell factor (p=0.09), and GM-CSF (p=0.09) to higher levels. The results of the current study indicate that Tr14 seems to limit exercise-induced muscle damage most likely via attenuation of both innate and adaptive immune responses. This study was registered with ClinicalTrials.gov (NCT01912469).